Gas Switching as a Practical Alternative for Scaleup of Chemical Looping Combustion. Issue 10 (7th July 2016) - Cloete, Schalk; Gallucci, Fausto; van Sint Annaland, Martin; Amini, Shahriar
Abstract: Gas‐fueled chemical looping combustion (CLC) requires high‐pressure operation to achieve competitive electric efficiencies. This work evaluates and compares two reactor concepts specially designed to reduce scaleup challenges under pressurized conditions: packed‐bed chemical looping combustion (PBCLC) and fluidized‐bed gas switching combustion (GSC). These concepts keep the oxygen carrier in a single dynamically operated reactor alternatively fed with air and fuel. Both concepts have been experimentally demonstrated and shown to achieve competitive performance in terms of electrical efficiency and CO2 avoidance. However, the PBCLC concept holds the greatest fundamental promise due to its behavior as a plug flow reactor. Substantial further material development and testing will be required to realize this potential. The GSC concept does not face such material‐related challenges, but requires reactor or plant modifications to achieve a performance that is competitive with the PBCLC concept. Abstract : Conditions for high process efficiency : Gas switching differs from conventional chemical looping by keeping the oxygen carrier in a single reactor where it is alternatively exposed to air and fuel. This paper compares two gas switching concepts based on packed‐ and fluidized‐bed reactor technology in terms of performance and scalability.